Knowledge and attitude about human papillomavirus vaccine among female high school students at Jimma town, Ethiopia - Tsegaw Biyazin; Ashenafi Yilma; Aynalem Yetwale; Belete Fenta; Yalemtsehay Dagnaw (Taylor & Francis Group, 2022)
Background The Human Papilloma Virus (HPV) is the primary causative agent of cervical cancer. HPV vaccination against human papillomavirus is more effective against cervical cancer. Therefore, this study aimed to investigate the knowledge and attitudes toward the human papillomavirus vaccines among female high-school students. Methodology This cross-sectional study was conducted among female high-school students in Jimma town, Ethiopia. Study participants were selected using a simple random sampling method. Self-administered interviews were conducted using a structured questionnaire. Data were entered using Epi-data version 3.5, exported and analyzed using the statistical package for the social sciences (SPSS) version 21. The Chi-squared (χ2) test was performed to determine the statistical significance between the outcome variable and independent variables. Results A total of 366 students participated in this study with a response rate of 94.8%. Only half (52.7%) and nearly one-third (31.4%) of the respondents had good knowledge and positive attitudes toward HPV vaccination, respectively. The predictors that included parents' educational status (χ2 = 1.479, P = .003), students participating in school mini-media (χ2 = 1.519, P = .036), students who had a smartphone (χ2 = 2.118, P = .008), availability of radio or television (TV) at home (χ2 = 2.163, P = .049), and students who received information from social-media (χ2 = 2.15, P = .025) were significantly associated with knowledge of the HPV vaccine. Conclusion Overall knowledge and attitude toward HPV vaccination were low. All concerned bodies should work jointly to enhance the knowledge and attitudes of female students toward Human Papilloma Virus vaccination.